Novel Thermally Reduced Graphene Oxide Microsupercapacitor Fabricated via Mask—Free AxiDraw Direct Writing - Vusani M. Maphiri; Gift Rutavi; Ndeye F. Sylla; Saheed A. Adewinbi; Oladepo Fasakin; Ncholu Manyala (Nanomaterials, 2021)
We demonstrate a simple method to fabricate all solid state, thermally reduced graphene oxide (TRGO) microsupercapacitors (µ-SCs) prepared using the atmospheric pressure chemical vapor deposition (APCVD) and a mask-free axiDraw sketching apparatus. The Fourier transform infrared spectroscopy (FTIR) shows the extermination of oxygen functional groups as the reducing temperature (RT) increases, while the Raman shows the presence of the defect and graphitic peaks. The electrochemical performance of the µ-SCs showed cyclic voltammetry (CV) potential window of 0–0.8 V at various scan rates of 5–1000 mVs−1 with a rectangular shape, depicting characteristics of electric double layer capacitor (EDLC) behavior. The µ-SC with 14 cm−2 (number of digits per unit area) showed a 46% increment in capacitance from that of 6 cm−2, which is also higher than the µ-SCs with 22 and 26 cm−2. The TRGO-500 exhibits volumetric energy and power density of 14.61 mW h cm−3 and 142.67 mW cm−3, respectively. The electrochemical impedance spectroscopy (EIS) showed the decrease in the equivalent series resistance (ESR) as a function of RT due to reduction of the resistive functional groups present in the sample. Bode plot showed a phase angel of −85° for the TRGO-500 µ-SC device. The electrochemical performance of the µ-SC devices can be tuned by varying the RT, number of digits per unity area, and connection configuration (parallel or series).